Potential of HfN, ZrN, and TiH as hot carrier absorber and Al2O3/Ge quantum well/Al2O3 and Al2O3/PbS quantum dots/Al2O3 as energy selective contacts. (10th July 2017) - Shrestha, Santosh; Chung, Simon; Liao, Yuanxun; Wang, Pei; Cao, Wenkai; Wen, Xiaoming; Gupta, Neeti; Conibeer, Gavin
Abstract: The hot carrier (HC) solar cell is one of the most promising advanced photovoltaic concepts. It aims to minimise two major losses in single junction solar cells due to sub-band gap loss and thermalisation of above band gap photons by using a small bandgap absorber, and, importantly, collecting the photo-generated carriers before they thermalise. In this paper we will present recent development of the two critical components of the HC solar cell, i.e., the absorber and energy selective contacts (ESCs). For absorber, fabrication and carrier cooling rates in potential bulk materials — hafnium nitride, zirconium nitride, and titanium hydride are presented. Results of ESCs employing double barrier resonant tunneling structures Al2 O3 /Ge quantum well (QW)/Al2 O3 and Al2 O3 /PbS quantum dots (QDs)/Al2 O3 are also presented. These results are expected to guide further development of practical HC solar cell devices.